The health service capacity of primary health care in West China: different perspectives of physicians and their patients - Wenjuan Tao; Wenqi Zeng; Ling Yan; Huazhen Yang; Jin Wen; Weimin Li (BMC, 2019)
Abstract Background Many countries, including China, have identified the primary health care system as a reform priority. The purpose of this study is to compare the perceived service capacity of primary care from the perspectives of physicians and their patients in Sichuan province of China. Methods A cross-sectional survey was conducted through Quality and Costs of Primary Care (QUALICOPC) questionnaires. A representative sample of 319 primary care physicians and 641 patients in 48 primary healthcare settings were recruited to take part in the study. Results Physicians perceived equity of care the best, while quality of care was rated the highest from the perspective of patients. They both regarded coordination as the weakest dimension of primary care service capacity. Conclusions Although primary health care reform may have been effective in helping patients acquire better primary care services, our results suggest that coordination is still perceived to be problematic for both physicians and patients. Improving the coordination of care has to be one of the main goals in the future primary care reforms in China.